2012
DOI: 10.1074/jbc.m111.337691
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effects of Systemic Administration of Chaperone αB-Crystallin Associated with Binding Proinflammatory Plasma Proteins

Abstract: Background: ␣B-Crystallin is therapeutic in animal models of multiple sclerosis and ischemia. Results: Crystallin binds ϳ70 plasma proteins; over half are members of the acute phase, coagulation, and complement pathways. Conclusion:The heat shock protein can bind with apparent selectivity and modulate inflammation. Significance: The capacity of the heat shock protein to bind a spectrum of ligands represents a unique therapeutic reagent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
99
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(103 citation statements)
references
References 35 publications
(34 reference statements)
2
99
0
2
Order By: Relevance
“…Inflammation is a state in which many stresses capable of inducing protein misfolding and aggregation are elevated; therefore, it is likely that proteostasis mechanisms will be enhanced during inflammatory events. Moreover, it has been shown that many acute-phase proteins are susceptible to stress-induced misfolding and major endogenous clients for holdase chaperones in human blood plasma (65)(66)(67). To survive periods of increased physiological stress, cells use several different strategies to prevent the accumulation of misfolded proteins (68)(69)(70)(71).…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation is a state in which many stresses capable of inducing protein misfolding and aggregation are elevated; therefore, it is likely that proteostasis mechanisms will be enhanced during inflammatory events. Moreover, it has been shown that many acute-phase proteins are susceptible to stress-induced misfolding and major endogenous clients for holdase chaperones in human blood plasma (65)(66)(67). To survive periods of increased physiological stress, cells use several different strategies to prevent the accumulation of misfolded proteins (68)(69)(70)(71).…”
Section: Discussionmentioning
confidence: 99%
“…In another manuscript (29) we have explored this hypothesis by defining the set of proteins HspB5 binds in plasma from patients with multiple sclerosis, rheumatoid arthritis, and amyloidosis. In each case, the sHsp precipitate was enriched relative to the normal plasma concentration with a set of ϳ65 proteins, over half of which are members of the acute phase, complement, and coagulation pathways.…”
Section: Tablementioning
confidence: 99%
“…Further analyses in these animal models concluded that the protein was immunosuppressive. The anti-inflammatory property was not due to influencing the adaptive immune response directly, but rather there was binding and resultant modulation of the proinflammatory mediators in plasma (29). These observations are at the basis of the therapeutic effects seen in both autoimmune and ischemic models of disease, including EAE, stroke, myocardial infarction, and retinal ischemia (25)(26)(27)(28).…”
mentioning
confidence: 91%
“…Meanwhile, Rothbard and another outstanding postdoc, Mike Kurnellas, had done structure function experiments narrowing the domains of amyloid proteins that might exert their immunesuppressive activity (89,90). Finally, Rothbard and Kurnellas realized that Eisenberg's amyloid fibril hexapeptides might indeed have immune-suppressive properties.…”
Section: Translational Research At Stanford Over the Past 20 Yearsmentioning
confidence: 99%
“…The amyloid structures bind inflammatory mediators in plasma (89)(90)(91). Amyloid hexapeptide structures elicit a type 1 interferon response (93).…”
Section: Translational Research At Stanford Over the Past 20 Yearsmentioning
confidence: 99%